Prevalence of metabolic syndrome in chronic obstructive pulmonary disease and its correlation with severity of disease - Kshiroda C Sahoo; Saswat Subhankar; Paresh C Mohanta; Suman K Jagaty; Pravati Dutta; Sudarsan Pothal (Journal of Family Medicine and Primary Care, 2022)
Introduction: The understanding of chronic obstructive pulmonary disease (COPD) has changed considerably over the past decade. The metabolic syndrome (MS) represents a cluster of risk factors that increases the risk for developing various noncommunicable diseases. In COPD, it is associated with worsening respiratory symptoms, increasing lung function impairment, pulmonary hypertension, and increasing hospitalizations. Aims: To determine the prevalence of MS in patients with COPD and correlate it with disease severity. Methodology: The present study was a cross-sectional observational study. Patients confirmed by spirometry to have COPD were included in the study. All demographic data and anthropometric, radiological, and laboratory parameters were recorded. The definition stated by modified NCEP ATP III criteria proposed by the AHA/NHLB (2005) was followed to identify patients with MS. Statistical analyses were performed using the Statistical Package for the Social Sciences (SPSS) version 20 for Windows. Results: A total of 76 patients were included in the study. MS was recorded in 42.1% of COPD cases. The average number of exacerbations and hospitalizations due to COPD in MS cases (1.38 ± 1.95 and 0.97 ± 1.51) were more than the patients without MS (1.27 ± 1.30 and 0.68 ± 0.96). The majority of patients with MS exhibited grade 3 dyspnea based on modified medical research council grading (MMRC). MS was commonest in patients with GOLD stage III disease. High serum triglyceride level was observed in an increasing trend (25%, 30%, 35.5%, and 75%) in GOLD stages I, II, III, and IV, respectively. Conclusion: Patients with MS present with more severe disease and frequent exacerbations. All COPD patients should be screened for MS at the primary level.